2016
DOI: 10.14744/anatoljcardiol.2016.6717
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the duration of mobile phone use on heart rate variability parameters in healthy subjects

Abstract: Objective:This study aimed to estimate the influence of the duration of mobile phone use on heart rate variability (HRV) in healthy individuals.Methods:One hundred forty-eight individuals without any established systemic disease and who had undergone 24-h ambulatory ECG monitoring were included in the case-control study. All the individuals had been using mobile phones for more than 10 years. Three-channel 24-h Holter monitoring was performed to derive the mean heart rate, standard deviation of normal NN inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
4
18
1
1
Order By: Relevance
“…Positive correlation between EFD and all CVDs we detected, as well as with OM of IHD, allows us to introduce a hypothesis on possible action of RF EMF of mobile communication terminals on functional status of CVS with consequent development of CVD, which is in accord with literature data [16][17][18]. Results we obtained when stratifying data on the principle of urbanization are concordant with the literature [5] and strengthen the hypothesis of electromagnetic environment influence on incidence of CVD.…”
Section: Discussionsupporting
confidence: 90%
“…Positive correlation between EFD and all CVDs we detected, as well as with OM of IHD, allows us to introduce a hypothesis on possible action of RF EMF of mobile communication terminals on functional status of CVS with consequent development of CVD, which is in accord with literature data [16][17][18]. Results we obtained when stratifying data on the principle of urbanization are concordant with the literature [5] and strengthen the hypothesis of electromagnetic environment influence on incidence of CVD.…”
Section: Discussionsupporting
confidence: 90%
“…We believe an interaction exists between the affected centres resulting in a delay of feedback which can increase HRV under 1:1 breathing and EMF exposure. This might be due to the excitation effect of cellular phone exposure on the brain (10), resulting in increased sympathetic activity in accordance with Braune et al (17) and Ekici and co-workers (37), considering also the relatively longer inspiratory period during the 1:1 breathing compared to the 1:2 pattern. During inhalation, respiratory sinus acceleration is a result of vagal withdrawal and increased sympathetic flow.…”
Section: Discussionsupporting
confidence: 77%
“…Other researchers came to similar conclusions regarding blood pressure and spectral HRV parameters in 120 volunteers (18). Upon habitual exposure to mobile phone radiation, the time domain HRV parameters were lower and the LF/HF ratio was higher, suggesting a shift to sympathetic activation compared to controls not using cellular phone at all (37).…”
Section: Discussionmentioning
confidence: 58%
“…Ekici et al concluded that HRV may be influenced by long-term mobile phone usage. [22] In our study, SDNN parameter did not show any significant difference between the 3 phases. While recording HRV time domain parameters, we found that RMSSD values were significantly reduced during direct contact of mobile phone to the ear and by use of earphones in comparison to baseline recording.…”
Section: Discussioncontrasting
confidence: 43%